Critically Explore Perceptions of Human Development in Classical Muslim Educational Thought and Discuss its Implications for Contemporary Islamic Education. - Idris Sidat (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Education is a contemporary social science that has received a lot of attention. As education defines society, it is imperative to introspect the philosophy of education. Moreover, the current philosophy of education in conventional settings is confined to empiricism. Thus, the broader concepts of education such as spiritual transformation and character reformation seem to be non-existent. The lack of discussion-based pedagogies compounds the educational crisis. This article aims to explore human development models relevant to Islamic education as its purpose is, alongside enhancing academic prowess, to provide spiritual transformation that leads to Gods pleasure and good character. The inquiry uses a historical-textual methodology with a particular focus on psychological foundations of Islamic theory to answer its questions. It will aim to explore childhood developmental models briefly and the concept of self-reflection more specifically and how it can be applied in Islamic education. The key findings of the study illustrate the concept of the three types of Nafs and how self-reflection is integral in achieving transformation, a concept that is condoned in conventional educational practice. Muhāsibī’s Risālatul Mustarshidīn with Shaykh Abdul Fattāh Abū Ghudda’s footnotes is the primary text used to establish the broader purpose of education. A brief overview of Qushayrī’s Risālah and Ibn Qayyim’s Kitābul Rūh will be outlined. Moreover, multiple attributes of human development conform to the demands of contemporary psychology to achieve a healthy mental transformation.